Genomic analyses reveal presence of extensively drug-resistant Salmonella enterica serovars isolated from clinical samples in Guizhou province, China, 2019–2023 - Yongxian Wen; Jingtong Wu; Lv You; Xiaoyu Wei; Junhua Wang; Shijun Li (Frontiers in Microbiology)
BackgroundThe emergence of extensively drug-resistant (XDR) Salmonella in humans poses a significant public health and therapeutic challenge. However, limited data are available on XDR Salmonella isolates from Guizhou province, China. This study aimed to investigate the molecular epidemiology and resistance patterns of XDR Salmonella isolates from clinical samples in this region.MethodsA total of 931 Salmonella isolates were screened for XDR isolates through antimicrobial susceptibility testing. These XDR isolates were subjected to whole-genome sequencing (WGS) and bioinformatic analysis to further systematically investigating the molecular epidemiology and resistance patterns of XDR Salmonella isolates.ResultsBetween 2019 and 2023, 931 Salmonella isolates were collected from clinical samples in Guizhou. Of these isolates, 51 (5.5%) were identified as XDR and classified into 16 serovars. Among the serovars, 15 corresponded to a specific sequence type, except for S. Typhimurium serovars. The predominant serovars, S. 1,4,[5],12:i:-, S. Enteritidis, and S. Kentucky, were divided into ST34, ST11, and ST198, respectively. Genomic analysis showed that all XDR isolates harbored at least eight antimicrobial resistance genes (ARGs) and multidrug efflux pumps. Highly prevalent point mutations in gyrA (D87 and S83) and parC (S80I) were detected, along with eight plasmid-mediated quinolone resistance (PMQR) genes. The qnrS1 gene was the most common (43.1%), followed by oqxA, aac-(6′)-lb-cr variant, qnrB4, qnrS2, qnrA1, qepA2, and oqxB. The predominant β-lactamase gene was blaTEM-1 (54.9%), and blaCTX-M-55 (35.3%) was the most prevalent extended-spectrum β-lactamase subtype. Notably, blaNDM-1 gene was identified for the first time in Salmonella from Guizhou, and one S. 1,4,[5],12:i:- isolate contained the mcr-1.1 gene. ARGs profiles varied by serovars, with S. 1,4,[5],12:i:- isolates carrying the highest number. Ten plasmid types were identified, predominantly IncHI2/IncHI2A (47.5%). Key resistance genes such as tetA, PMQR, blaCTX-M, mcr-1.1, and blaNDM-1 were located on IncHI2/IncHI2A plasmids. Notably, 75.0% of the conjugative plasmids belonged to IncHI2/IncHI2A, indicating that horizontal gene transfer through conjugation facilitates ARGs dissemination. Core genome multilocus sequence typing (cgMLST) analysis revealed significant genetic diversity, with 39 core genome sequence types (cgSTs) identified and no evidence of outbreaks.ConclusionThe rising prevalence of XDR Salmonella in Guizhou province is concerning. Initial whole-genome sequencing (WGS) data provide critical insights for understanding and controlling XDR Salmonella infections, aiding public health officials in identifying emerging threats and trends.